DILEMA TROTOAR Studi Kasus Dampak Pembangunan Trotoar terhadap Pedagang Kaki Lima di Salatiga - Khosasi, Amos Mario; Kusumaningtyas, Dita Mawar; Halsted, Theodore; Sasongko, Gatot (KRITIS, 2018)
The existence of street vendors can reduce the burden of government in overcoming unemployment. Due to the existence of street vendors, can absorb labor that can not be accommodated by the formal sector. But on the other hand, the presence of street vendors often disrupt the activities in the public sphere area such as sidewalks. Therefore, the government of Salatiga City made a policy by improving the function of the sidewalk and sterilize it to be enjoyed again by pedestrians. But with the sterilization, the impact also to the street vendors, which they should move. The purpose of this study is to determine the impact caused by the construction of the sidewalk to the income level of street vendors. In conducting this research, we conducted interviews with several street vendors who are still actively selling. Among other things, soto traders,chicken noodles, and leker. The results showed that the impact of pavement development had a negative impact on the income level of street vendors. Also found obstacles that arise after the street vendors are moving places, such as infrastructure facilities are not met, inadequate facilities, and reduced visitors who come.